Water pinch analysis for water management and minimisation: an introduction - Wan Alwi, S. R. (Elsevier Inc., 2013)
This chapter describes approaches for water management and minimisation based on the Water Pinch Analysis (WPA) concept. The chapter presents the step-wise procedure for implementing WPA. The significance of WPA and its applications in the industrial sector are also discussed.